For every positive integer g there is a unique factorial base expansion ( g 1 , g 2 , g 3 , … , g m ) , meaning that
g = 1 ! ⋅ g 1 + 2 ! ⋅ g 2 + 3 ! ⋅ g 3 + ⋯ + m ! ⋅ g m , where each g i is an integer, 0 ≤ g i ≤ i , and 0 < g m .
Given that ( g 1 , g 2 , g 3 , … , g j ) is the factorial base expansion of 1 6 ! − 3 2 ! + 4 8 ! − 6 4 ! + ⋯ + 1 9 6 8 ! − 1 9 8 4 ! + 2 0 0 0 ! , find the value of g 1 − g 2 + g 3 − g 4 + ⋯ + ( − 1 ) j + 1 g j .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
That is not the number under consideration in the problem.
Problem Loading...
Note Loading...
Set Loading...
Write the number N = ( 2 0 0 0 ! − 1 9 8 4 ! ) + ( 1 9 6 8 ! − 1 9 5 2 ! ) + ⋯ + ( 4 8 ! − 3 2 ! ) + 1 6 ! . It is well known that n ! − 1 = k = 1 ∑ n − 1 k ⋅ k ! , so that n ! − m ! = k = 1 ∑ n − 1 k ⋅ k ! − k = 1 ∑ m − 1 k ⋅ k ! = k = m ∑ n − 1 k ⋅ k ! . Thus we have N = ( 1 9 9 9 ⋅ 1 9 9 9 ! + ⋯ + 1 9 8 4 ⋅ 1 9 8 4 ! ) + ( 1 9 6 7 ⋅ 1 9 6 7 ! + ⋯ + 1 9 5 2 ⋅ 1 9 5 2 ! ) + ⋯ + ( 4 7 ⋅ 4 7 ! + ⋯ 3 2 ⋅ 3 2 ! ) + 1 6 ! In other words, g i = ⎩ ⎪ ⎨ ⎪ ⎧ 1 i 0 i = 1 6 i ≡ 0 , … 1 5 mod 3 2 otherwise Now to do the final calculation. Note that 4 7 − 4 6 + 4 5 − 4 4 + − ⋯ − 3 2 = ( 4 7 − 4 6 ) + ⋯ + ( 3 3 − 3 2 ) = 8 ⋅ 1 = 8 ; There are 1 9 8 4 / 3 2 = 6 2 of these runs of 16 non-zero values, so that the final answer is 6 2 ⋅ 8 − 1 = 4 9 5 . (The final 1 is the term g 1 6 .)